School Management Strategies to Improve Parental Involvement: Insights from School Principals in Southern Tshwane Primary Schools (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
Parental involvement plays a very important role in the development of a child's formal education. Even though there are many benefits of parental involvement, there are many factors that constrain parental involvement. This study explored various management strategies that might serve as guidelines to improve parental involvement in Southern Tshwane primary schools. The conceptual framework that informed this study was Factors that Determine School Effectiveness by Heneveld and Craig as well as Epstein's theory of overlapping spheres and her typology on parental involvement that served as the theoretical framework for this study. A qualitative research approach was the method used for this study, as it allowed the researcher to conduct in-depth interviews with six principals in Southern Tshwane primary schools. An extensive literature study and relevant documents were also examined to collect rich and comprehensive information. The research indicates that most schools comprehend the importance of parental involvement, yet lack structured implementation frameworks for parental involvement. The study recommends that schools need to plan, manage and implement a parental involvement programme according to the unique circumstances of the school.